An Application of Prony's Sum of Exponentials Method to Pharmacokinetic Data Analysis (Communications in Computational Physics, 2007)
We discuss the basic concept of compartmental modelling in pharmacokineticsand demonstrate that all the solutions admitted by multi-compartment modelsof classical pharmacokinetics are expressed as linear combinations of exponentialfunctions of time. This lends itself to data analysis that depends on fitting exponentialfunctions to finite size sets. A mathematical method developed a long time ago to dealwith this type of problem is called Prony's method. We discuss the usefulness of thismethod in pharmacokinetic modeling and apply it to a particular data set obtainedfor the drug mibefradil. In spite of the method's power in dealing with well-behaveddata sets, we indicate the existence of severe limitations since real concentration curvescoming from pharmacokinetic data are seldom purely exponential.